Radiology Illustrated: Gynecologic Imaging - Kim, Seung Hyup (Radiology Illustrated,, 2012)
Radiology Illustrated: Gynecologic Imaging is an up-to-date, image-oriented reference in the style of a teaching file that has been designed specifically to be of value in clinical practice. Individual chapters focus on the various imaging techniques, normal variants and congenital anomalies, and the full range of pathology. Each chapter starts with a concise overview, and abundant examples of the imaging findings are then presented. In this second edition, the range and quality of the illustrations have been enhanced, and image quality is excellent throughout. Many schematic drawings have been added to help readers memorize characteristic imaging findings through pattern recognition. The organization of chapters by disease entity will enable readers quickly to find the information they seek. Besides serving as an outstanding aid to differential diagnosis, this book will provide a user-friendly review tool for certification or recertification in radiology.